METHOD OF VIRTUAL SPATIAL MANIPULATION IN TEACHING OF MATHEMATICS - ZILKOVA, Katarina (Journal of Technology and Information Education, 2009)
Teaching of mathematics in the context of information and communication technologies requires not only the innovation of traditional teaching methods, but also spurred the creation of new teaching practices. The contribution clarifies the principle of virtual spatial manipulation, as an important teaching method aimed at promoting development of spatial imagination. An overview of mathematics and geometry software suitable for solving of spatial problems gives their short characteristics together with suggestions for use. Usefulness of the use of virtual methods of spatial manipulation is illustrated by solving a simple spatial problem in the Cabri 3D environment.
Keywords: dynamics; geometry; interactivity; manipulation; spatial situation; virtual manipulation.